REQUEST STRATEGIES USED BY INTERNATIONAL STUDENTS IN ENGLISH AS A LINGUA FRANCA CONTEXT - Situmorang, Komilie (Sanata Dharma University Yogyakarta, 2022)
This study explored the permeating strategies used by the international student in request acts and the common features appearing during the language use as international students in Indonesia, where English is used as a Lingua Franca. The study employed a set of Oral Discourse Completion Test (ODCT) to collect the data from eight international students. Ten ODCTs were composed based on the relative power, social distance, and imposition and were analysed based on the Cross-Cultural Study of Speech Act Realization Patterns (CCSARP). The result was presented in descriptive qualitative where the most frequently used strategies were conventionally indirect – suggestory formulae. Meanwhile, the content analysis indicated that address terms and lengthy reasonings were the most common features appearing in the request acts made. The results offer that interlanguage pragmatic in lingua franca context occurs smoothly as the international students can combine the local culture in their language use.